COLEOPTERA LAMELLICORNIA DE LA SIERRA DEL TENTZO, PUEBLA, MEXICO - Angel Morón, Miguel Ángel; Aragón, Agustín; Tapia Rojas, Ana María; Rojas García, Raúl (Instituto de Ecología, A.C., 2000)
Preliminary analysis of the scarab beetle fauna of the mountains of Tentzo, Puebla, México is presented. Data were obtained during 1996-1997 with 92 days of collecting effort in oak forest, deciduous tropical forest and thorn shrubs, between 2,000-2,350 m altitude. Records of 8 subfamilies, 14 tribes and 49 species of the genera Phyllophaga, Diplotaxis, Anómala, Ligyrus, Golofa, Strategus, Xyloryctes, Euphoria, Canthon, Sisyphus, Phanaeus, Coprophanaeus, Dichotomius, Onthophagus, Euoniticellus, Ochodaeus, Aphodius, Ataenius and Trox are included. Specific diverslty is concentrated in the genera Phyllophaga (12 spp.) and Diplotaxis (9 spp.). Phyllophaga ravida (Blanch.) was the most abundant species in the samples. Golofa tepaneneca Morón is confirmed as an endemic species for these mountains. Sisyphus submonticolus Howden and Euoniticellus intermedius Reiche are cited for the first time in the State of Puebla. The scarab beetle fauna of Tentzo area shows equilíbrate similarity with the Puebla valley (27%) and the Balsas river upper slopes (21 %), while the similarity with the Gulf of México slopes is much lower (8 %).